Cardiac Drug Therapy - Khan, M. Gabriel (Contemporary Cardiology,, 2015)
This book is an essential guide to the medical treatment of the cardiac patient and presents core principles of cardiovascular therapeutics as well as drug recommendations. Major classes of drugs are featured, including beta-blockers, ACE inhibitors, calcium antagonists, diuretics, and antiplatelet agents and unique insights into the controversies surrounding the use of specific drugs are explored, with answers given to the question: do beta blockers and diuretics really cause diabetes? Properties, dosage, side effects, potential salutary benefits, and drawbacks on virtually all commercially available cardiac drugs are examined. This revised edition is thoroughly updated and addresses the entire spectrum of heart disorders, such as hypertension, angina, myocardial infarction, heart failure, arrhythmias, cardiac arrest, and dyslipidemias. New chapters include endocrine heart diseases, management of cardiomyopathies, and newer agents. In addition, topics such as cardiac drugs in pregnancy and lactation and drug interactions are covered. Cardiac Drug Therapy, Eighth Edition, is an authoritative and clinically relevant resource for cardiologists, cardiology fellows, and internists.